The Loyal Opposition & The Practice of Aikido - Miller-Lane, Jonathan (Revista de Artes Marciales Asiáticas, 2012)
<span style="mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-font-weight: bold;" lang="EN-US">Discussions regarding martial arts often focus on the unique manner in which different styles respond to a set of common attacks. Indeed, it is in these unique responses that most martial arts distinguish themselves. However, this paper examines the role of the aggressor during training; specifically, in the martial art of Aikido and draws an analogy between the role of an aggressor during Aikido practice and the actions of a member of the loyal opposition in a democracy. A commitment to a set of rules that govern and protect the participants and a commitment to maintain a rich, creative tension mark both the vibrant interactions of an Aikido dojo and democratic life in a multicultural society.